KORELASI FAKTOR PREDISPOSISI DENGAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) - Putra, Bayu Pratama; Qamarya, Nurul; Andriani, Rininta; Multazam, Andi Muhammad (Ensiklopedia of Journal, 2024)
Abstract: The coverage of the use of long-term contraceptive methods (MKJP) in the work area of UPT Puskesmas Kampung Sawah in 2021 was only 16.21%. It is feared that the low use of MKJP can increase the family planning dropout rate and maternal and child health problems. The purpose of the study was to determine the correlation of predisposing factors with the use of long-term contraceptive methods (MKJP). This study is a quantitative study with a cross sectional study design. The research was conducted in the work area of UPT Puskesmas Kampung Sawah in December 2022. The research sample amounted to 156 women of childbearing age (WUS) who were selected using simple random sampling. The research instrument used a research questionnaire. The analysis conducted was univariate and bivariate analysis. The results showed that there was a relationship between parity (p value: 0.001) and the use of MHCP. It is recommended that PUS can play an active role in every family planning activity, diligently consult with health workers, and independently seek information through trusted social media, so as to obtain better knowledge about contraceptives.Keywords: Information Exposure, Knowledge, SADARI